1992
DOI: 10.3109/00016489209137479
|View full text |Cite
|
Sign up to set email alerts
|

The Middle Ear as a Baroreceptor

Abstract: Under pressure in the middle ear is thought to be important in the pathogenesis of chronic otitis media with effusion and its sequelae, but the cause of the under pressure and the mechanisms responsible for regulation of the normal middle ear pressure are a matter of debate. Numerous studies have examined the effect of large pressure changes on the ear; however, the ear's sensitivity to smaller pressure changes has received little attention. This study examines the sensitivity of the ear to atmospheric air pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Some authors suggested that the special area (viz., pars flaccida) in the tympanic membrane containing elastin fibers is actually a sensor mechanism for pressure fluctuations in the middle ear [23,24]. In favor of this view, the mechanical reactions of pars flaccida in response to very little changes in the middle ear pressure, as well as to slight pressure oscillations in far infrasound range, were demonstrated by the experimental studies on animals [25,26].…”
Section: Discussionmentioning
confidence: 70%
“…Some authors suggested that the special area (viz., pars flaccida) in the tympanic membrane containing elastin fibers is actually a sensor mechanism for pressure fluctuations in the middle ear [23,24]. In favor of this view, the mechanical reactions of pars flaccida in response to very little changes in the middle ear pressure, as well as to slight pressure oscillations in far infrasound range, were demonstrated by the experimental studies on animals [25,26].…”
Section: Discussionmentioning
confidence: 70%
“…Considering the atmospheric infrasonics as an acoustic phenomenon, Green and Dunn (1968) supposed that they could affect the human body through the ear. It has been also suggested that fast variations in ambient pressure could be registered by stretch receptors in the middle ear cavity (Rockley and Hawke 1992).…”
Section: Discussionmentioning
confidence: 99%
“…There is also physiological evidence of active regulation mechanisms in that unilateral electric stimulation of the tympanic nerve in monkey has been shown to evoke bilateral electromyographic responses from Eustachian tube muscles (Eden et al 1990). Moreover, Rockley and Hawke (1992) and Sakata et al (2009) have shown that application of lidocaine hydrochloride to anesthetize the human tympanic membrane substantially increases the behavioural threshold for detecting pressure changes across the tympanic membrane.…”
Section: Introductionmentioning
confidence: 99%